PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA APARATUR SIPIL NEGARA DI KANTOR KECAMATAN KAWANGKOAN UTARA - TENDA, PINGKAN; RARES, JOYCE; LONDA, VERY (Sam Ratulangi University, 2018)
Abstract: Organizational culture is a system of shared meanings embraced by members who emphasizeorganization with other organizations. Performance is the level of success in achieving goals. It is said that thesuccess of the goals as desired. Government apparatus is required to improve performance and develop. Theresearch method that writer use in this research is quantitative research method, With formulation of problem